Adaptive control for a class of MIMO nonlinear time delay systems against time varying actuator failures. (July 2015) - Hashemi, Mahnaz; Ghaisari, Jafar; Askari, Javad
Abstract: This paper investigates an adaptive controller for a class of Multi Input Multi Output (MIMO) nonlinear systems with unknown parameters, bounded time delays and in the presence of unknown time varying actuator failures. The type of considered actuator failure is one in which some inputs may be stuck at some time varying values where the values, times and patterns of the failures are unknown. The proposed approach is constructed based on a backstepping design method. The boundedness of all the closed-loop signals is guaranteed and the tracking errors are proved to converge to a small neighborhood of the origin. The proposed approach is employed for a double inverted pendulums benchmark and a chemical reactor system. The simulation results show the effectiveness of the proposed method. Highlights: The control problem is investigated for a class of MIMO nonlinear time delay system in the presence of time varying actuator failures. The considered actuator failures are unknown stuck types. A differentiable function is used to avoid the singularity problem of the controllers. Appropriate Lyapunov-Krasovskii functionals are introduced to design new adaptive laws. The proposed method proves that all the closed loop signals are bounded and the tracking errors converge to a small neighborhood of the origin.